Tradisi Intelektual dalam Tamadun Islam Alam Melayu: Analisis Kitab Melayu Klasik Abad ke-17 hingga ke-19: Intellectual Tradition of Islamic Civilization in the Malay World: An Analysis of Classical Malay Works from the 17th to the 19th Century - Abdul Malik, Mohd Pua’ad; Abdul Hamid, Faisal @ Ahmad Faisal; Abd. Rahim, Rahimin Affandi (Journal of Al-Tamaddun, 2025)
This study examines the typology of classical Malay fiqh writings produced in the Malay World from the seventeenth to the nineteenth centuries. Accordingly, the study aims to identify and categorise these works based on two principal approaches: chronological analysis and analysis of writing methodology. Employing a comprehensive content analysis method, the study maps the patterns and evolution of fiqh writing. The findings successfully identify distinct patterns within the writing tradition, revealing significant developments in terms of methodology and the diversity of subjects addressed. These findings demonstrate the intellectual dynamism that shaped the Islamic scholarly heritage of the region. In summary, this study contributes to a deeper understanding of Islamic intellectual history in the Malay World. It not only provides new insights into the evolution of fiqh but also highlights the intellectual contributions of Malay scholars in shaping a progressive form of Islamic legal thought that is responsive to local contexts.